Improving soil physical properties and yield of mustard greens through vermicompost and nitrogen application - Sukerta, I Made; Pratiwi, Ni Putu Eka; Ananda, Komang D.; Ramdhoani, Ramdhoani; Limantara, Lily M. (Journal of Water and Land Development, 2026)
This study evaluated the effects of combined vermicompost and nitrogen fertilisation on soil physical properties and the yield of mustard greens (Brassica juncea L.) cultivated under coastal dryland conditions in Jungutbatu Village, Nusa Lembongan, Bali, Indonesia. The experiment was conducted during a single growing season using a factorial randomised block design with six vermicompost rates (0–25 Mg∙ha−1) and four nitrogen levels (0–138 kg N∙ha−1), each replicated three times. Vermicompost was incorporated into the soil prior to planting, while nitrogen was applied as urea during crop growth. Plant growth parameters, biomass yield, and selected soil physical and chemical properties were assessed. The combined application of vermicompost and nitrogen significantly affected the plant height, leaf area index, and total biomass yield. The highest fresh (238.52 Mg∙ha−1) and oven-dried biomass (12.53 Mg∙ha−1) were obtained with 25 Mg∙ha−1 vermicompost combined with 138 kg N∙ha−1. Improvements in soil porosity and permeability, and reductions in bulk density, were also observed as accompanied by increases in soil organic carbon and total nitrogen. Regression analysis indicated predominantly linear responses of biomass yield to increasing fertiliser doses, suggesting additive rather than synergistic effects under the conditions of this study. These findings demonstrate the short-term potential of integrated organic and inorganic fertilisation to improve mustard productivity and soil physical quality in nutrient-poor coastal drylands. However, further multi-season and multi-site studies are required to evaluate the long-term soil effects, environmental risks, and the economic feasibility of high vermicompost application rates.